Mismatch between observed and perceived upper limb function: an eye-catching phenomenon after stroke. Issue 13 (19th June 2019) - Essers, Bea; Meyer, Sarah; De Bruyn, Nele; Van Gils, Annick; Boccuni, Leonardo; Tedesco Triccas, Lisa; Peeters, André; Thijs, Vincent; Feys, Hilde; Verheyden, Geert
Abstract: Purpose: To investigate the relation between observed and perceived upper limb motor function in patients with chronic stroke. Material and methods: We investigated 32 patients at six months after stroke with the Fugl-Meyer Assessment (observed function) and hand subscale of the Stroke Impact Scale (perceived function). Spearman correlation was calculated to relate observed and perceived function. Through cut-off scores, we divided our sample in low (Fugl-Meyer Assessment <31/66) and good observed function, and low (hand subscale of Stroke Impact Scale <61/100) and good perceived function. Scatterplot and hierarchical clustering analysis was conducted to detect distinct groups. Results: A strong positive relation was found between observed and perceived function ( r  = 0.84). Three groups could be identified; a "low match group" of patients with low observed and low perceived function ( n  = 11, 34%), a "good match group" containing patients with good observed and good perceived function ( n  = 15, 47%), and a "mismatch group" comprising patients with good observed but low perceived function ( n  = 6, 19%). Conclusions: In our chronic sample, one in five patients showed good upper limb observed but low perceived function. Measuring both observed and perceived arm and hand function seems warranted together with considering a differential therapy approach for the distinct groups. Implications for rehabilitation: A considerable group of patients in the chronic phase post-stroke have good motor function in their affected upper limb, but nevertheless perceive a restricted ability. In order to identify a mismatch in people with chronic stroke, both observed and perceived upper limb motor function should be assessed. Besides common measurement tools for observed function like the Fugl-Meyer Assessment, perceived function can be evaluated by means of the hand function section of the Stroke Impact Scale. For patients with good observed but low perceived function, an additional rehabilitation strategy should be considered, potentially including awareness of ability and a self-efficacy approach.